Pengaruh Biaya Produksi Terhadap Omset Penjualan Kopi Toraja: (Studi Kasus Kopi Salu Sopai di Kecamatan Rantepao) (Lembaga Pengembangan Kinerja Dosen, 2023)
This study used a questionnaire distributed to employees at Kopi Salu Sopai, North Toraja Regency with a total sample of 16 respondents. Sampling using purposive sampling. The data analysis technique used is multiple linear regression analysis. From the test results it is known that raw material costs have a significant effect on sales turnover. Labor costs have a significant effect on sales turnover. Factory overhead costs have a significant effect on sales turnover. Simultaneously show so that raw material costs, labor costs and factory overhead costs simultaneously affect sales turnover.